Development of a new family of monolithic calcium (pyro)phosphate glasses by soft chemistry. (1st September 2016) - Soulié, Jérémy; Gras, Pierre; Marsan, Olivier; Laurencin, Danielle; Rey, Christian; Combes, Christèle
Graphical abstract: Abstract: The development of bioactive phosphate-based glasses is essential in biomaterials science, and especially for bone substitution applications. In this context, the preparation of amorphous calcium-phosphorus hydroxide/oxide monoliths at low temperature is a key challenge for being able to develop novel hybrid materials for these applications. We herein report for the first time the synthesis and physical chemical characterisation of a novel family of pyrophosphate-based glasses (with the formula: {[(Ca 2+ )1−x (H + /K + )2x ]2 [(P2 O7 4− )1−y (PO4 3− )4y/3 ]} n(H2 O)), which were prepared by soft chemistry using low temperatures (T < 70 °C) and water as a solvent. The effect of the initial Ca/Pyrophosphate ratio on the structure and morphology of these pyrophosphate glasses was investigated in detail. Depending on this ratio, a glass (mixed calcium pyro- and orthophosphate) or a glass-ceramic (Ca10 K4 (P2 O7 )6 ·9H2 O crystals embedded in the amorphous phase) was obtained. The proportion of the crystalline phase increased with an increase in the Ca/Pyrophosphate ratio in the batch solution. As expected for a glass, the formation of the glassy material was demonstrated not to be thermodynamically but rather kinetically driven, and the washing step was found to be crucial to prevent crystallisation. The stability of the amorphous phase was discussed considering the structural degrees of freedom of pyrophosphate entities, ionic strength of the initial solution and the inhibitory effect of orthophosphate ions. Overall, this new strategy of preparation of monolithic calcium-(pyro)phosphate based glasses using soft chemistry in water is highly promising in view of preparing new functional organic-inorganic hybrids for bone substitution applications. Statement of Significance: Phosphate-based glasses have gradually emerged as a potential alternative to silicate bioactive glasses in order to induce different biological mechanisms of degradation. The synthesis of such monolithic glasses at low temperature is a key step to allow new inorganic glass compositions to be reached and hybrid materials to be prepared. Although sol-gel and coacervate methods (respectively orthophosphate and metaphosphate precursors) have already been described to prepare such glasses, the use of toxic solvents and/or the final temperature treatment associated to these processes could limit the use of these materials for biomedical applications and/or the further development of hybrids. It is shown here that pyrophosphate precursors are an alternative strategy to obtain monolithic calcium (pyro)phosphate glasses under soft conditions (water solvent, 70 °C).